purification of RAVE complex from Saccharomyces cerevisiae using FLAG tag-affinity purification method - Thanh Trung, Nguyen; Thi Tam, Pham; Thi Thu Thuy, Ta; Gu, Chunyin; Zhang, Zhenyu (Vietnam Journal of Science and Technology, 2017)
RAVE (Regulator of the H+-ATPase of the Vacuolar and Endosomal membranes) is an essential factor of assembly and reversible disassembly of V-ATPase. RAVE complex has three subunits, which are Rav1p, Rav2p and Skp1p. There are few studies on RAVE so it is very important to study structure of RAVE complex to understand more about the regulation of the assembly and reassembly at V-ATPase. In this study the RAVE complex was purified by affinity purification by fussing FLAG tag to subunit Rav1p or Rav2p. Experimental process: yeast cells were incubated in 8 L YEPD medium at 30 oC, 200 rpm (OD600nm around of 3). Furthermore harvested cells were broken by a French pressure cell disruptor at 25,000 p.s.i in TBSE (50 mM Tris/Cl, 150 mM NaCl, 1 mM EDTA, pH 7.4) with 1 mm PMSF. The cell lysate was centrifuged at 20,000 xg for 20 minutes at 4 oC. Then, the supernatant, was achieved by centrifugation, and loaded onto a small column contained 1 ml of anti-FLAG M2 gel. After washing anti-FLAG column with TBSE, RAVE complex was eluted with TBSE containing 100 µg/ml FLAG peptides. The results showed RAVE complex purification from strain with FLAG tag fused in C-terminus of Rav2 is better than RAVE complex purification from the yeast strain S. cerevisiae with FLAG tag fused in N-terminus of Rav1 or C-terminus of Rav1.